APPLICATIONS RESERVATION ON PRINTING LANE USING VISUAL BASIC 6.0 - Haeza Fadilla; Rahayu Noveandini SKom,MM (Jurnal Sistem Informasi, 2008)
Along with the rapid the development era increasingly complex problems which faced humans. The necessity to solve a problem with cepet, preciseand efficient is which very required. Because of that science and technology information always developed for make it happen. One of them in printing area on process ordering of goods. In this writing author make system computerization to the reservation goods on Printing Line. Which equipped with FOD, DFD, ERD, Normalization about application made. Program existing on This application is comprised of the main menu which display Data menu, the menu of transactions, reports menu. Where Data menu there sub menu input data goods and input data orders. Menu transaction there sub nota menu. Whereas there are reports menu sub orders and sub-menu report reports menu memorandum. Where menu This report is used to display and print reports. Application system this aims to replace the system which manual with system which already computerized, with the hope of make way work company to be better especially on the reservation.Keywords: Application, Booking Goods